Chiral Carbon Dots: Synthesis and Applications in Circularly Polarized Luminescence, Biosensing and Biology. Issue 1 (20th January 2023) - Yan, Xuetao; Zhao, Huijuan; Zhang, Ke; Zhang, Zhiwei; Chen, Yingying; Feng, Lingyan
Abstract: Chiral carbon dots (CDs) are a novel luminescent zero‐dimensional carbon‐based nanomaterial with chirality. They not only have the advantages of good biocompatibility, multi‐color‐emission, easy functionalization, but also exhibits highly symmetrical chiral optical characteristics, which broadens their applicability to enantioselectivity of some chiral amino acids like cysteine and lysine, asymmetric catalysis as well as biomedicine in gene expression and antibiosis. In addition, the exploration of the excited state chirality of CDs has developed its excellent circularly polarized luminescence (CPL) properties, opening up a new application scenario like recognition of chiral light sources and anti‐counterfeit printing with information encryption. This review mainly focuses on the mature synthesis approaches of chiral CDs, including chiral ligand method and supramolecular self‐assembly method, then we consider emerging applications of chiral CDs in CPL, biosensing and biological effect. Finally, we concluded with a perspective on the potential challenges and future opportunities of such fascinating chiral CDs. Abstract : Chiral carbon dots (CDs) are a new type of chiral zero‐dimensional nanomaterials, and this review focuses on the preparation and application of chiral CDs. The preparation methods can be divided into chiral ligand method and supramolecular self‐assembly method, and the applications are mainly concentrated on chiral CDs in circularly polarized luminescence, biosensing and bioeffects.